The effects of power on life in Michel Foucault’s biopolitic device - Agustina Alejandra Andrada (HYBRIS: Revista de Filosofía, 2019)
This work explores the first part of the foucaultian formula to describe biopolitics, that is, the biopolitic “make live”. This analysis seeks to understand the way in which power relates to peoples’ lives, which are its strategies, its devices and its effects. For that matter, it abides first in the concept of life in biopolitics, taking Foucault’s analysis on biology. Secondly, the goal is to review the practices used by such technology to modify vital phenomena in pursuit of its government interests